MORPHOLOGICAL CHANGES IN THE PROPRIOCEPTORS OF HUMAN ANTERIOR CRUCIATE LIGAMENT DURING DEGENERATIVE OSTEOARTHRITIS - Iskren Gerasimov; Stefan Trifonov; Desislava Marinova; Aleksandar Todorov; Iliyana Vacheva; Savelina Popovska; Asparuh Asparuhov; Ivan Ivanov (Peytchinski Publishing, 2019)
Introduction/Aim: The anterior cruciate ligament (ACL) of the knee joint is one of the most investigated structures of the musculoskeletal system. Numerous studies are dedicated to the macro- and micro anatomy of human and animal ACL, but not many are focused on the proprioceptors of the ligament. The aim of this study was to establish a relationship between the proprioceptors and the stage of degenerative changes in the ACL. Materials and Methods: Sixty ACL were harvested from patients admitted for knee replacement surgery. The samples were processed, histochemically and immunohistochemically stained according to standard laboratory protocols. Results were analysed and interpreted. The research was approved by the Ethics Committee of Medical University Pleven. Results: Fifty-seven patients were included in our study - 37 females and 20 males. The average age of patients was 66.48 years. Degeneration of ACL was classified in four stages, and four different patterns of degeneration were observed: 1) necrosis and inflammation; 2) myxoid and cystic formation; 3) vascularisation with myxoid changes; 4) inflammation and hyalinosis. With the increasing severity of degeneration, the number of specialized nervous structures diminish. Discussion: Our findings support the results from studies on animal models, conducted by other authors. Cabuk et al. reported a diminishing number of proprioceptors in the PCL of an osteoarthritic human knee.The lower number of proprioceptors could result in the onset or progression of the arthritic process. Conclusion: Osteoarthritis involves all elements of the knee joint. Altered proprioception could be the reason for unsatisfied patients with artificial knees.